Reimagining inclusive education from the margins: Multi-sectoral collaboration and spatial justice in Rural Bali - Hendrawati, Sri; Pamungkas, Onok Yayang; Widaryanto, Benny; Marjanto, Damardjati Kun; Suarbhawa, I Gusti Made; I Ketut Sudharma Putra (Research Journal in Advanced Humanities, 2025)
This study critically explores the dynamics of inclusive education in Bengkala, Bali. It situates inclusion as a socio-spatial practice that is continuously negotiated through intersecting relations of power, culture, and geography. Using critical-interpretive qualitative methodology, this study combines ethnographic investigation, document analysis, and spatial mapping (GIS) to examine how multi-sectoral collaboration. The findings of this study suggest that although grassroots actors act as epistemic connectors, the institutionalization of inclusion remains fragile, uneven, and highly dependent on relational infrastructures. Furthermore, spatial analysis reveals how geographic exclusion persists under the guise of formal inclusivity, especially for marginalized hamlets that are beyond the reach of infrastructure support. By combining Critical Inclusion Theory, interdisciplinary collaboration models, and spatial justice frameworks, this study offers a conceptual overview of inclusive education that listens from the margins and centers lived experience as an epistemic resource in shaping ethical and place-based inclusion. These findings imply that inclusive policy frameworks must move beyond institutional mandates towards place-sensitive and socially negotiated models that recognise grassroots agency.